The Actor's Relationship to the Traditional Government of Parlondut Samosir Village - Yohansen Wyckliffe Gultom; Tonny P. Situmorang; Bengkel Ginting (Universitas Medan Area, 2023)
The relationship between actors at the village level in Indonesia often changes in each period. The uniformity of actors in Indonesia has finally begun to take place since the enactment of Law No. 5 of 1979 concerning Village Government. This study wanted to look at the relationship of actors at the village level. Especially in Parlondut Village, Samosir Regency. This research is qualitative research with qualitative descriptive methods and data collection techniques in the form of in-depth interviews along with literature studies. The results of this study show that there are differences in dominance between actor relations (power over relations) in each period of power at the village level. In addition, from the aspect of relations or values (power to relation) there is a value order that is still maintained, such as Dalihan Na Tolu and marsiadapari which lasted since the traditional reign of Ancient Batak, the Dutch period, Japan including during the Old Order through the huta and habius governments. As a conflict resolution in the midst of conflict at the Parlondut village level, Samosir Regency is recognized as an indigenous community but not as an indigenous village because there must be supporting regulations at the district level.